Innovative Equipment to Monitor and Control Salt Usage When Cooking: Acceptance of This New Technology to Healthy Eating Promotion - Gonçalves, C. (2021)
A large number of studies support the concept that high salt intake is the main risk factor in increasing blood pressure and cardiovascular diseases in the population. The main objective of this study is to analyze consumers preliminary satisfaction questionnaires regarding the use of an innovative prototype equipment to monitor and control salt during cooking the Salt Control H (SCH) during their participation in one clinical trial. Most of the participants (37.5%) reported that stayed very satisfied with the use of the equipment (overall satisfaction) and 78.1% of participants would like to recommend the SCH to a friend. This acceptance study shows satisfactory results, even though it is a prototype version, to encourage the use of this innovative equipment in order to improve familys tools to healthier cooking. (c) 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.